A SEMIOTIC ANALYSIS ON NEWS PHOTOGRAPHS IN THE JAKARTA GLOBE ONLINE NEWSPAPER REGARDING THE TRAGEDY OF MASSIVE DEMONSTRATION IN EGYPT - Fini Fitriani, - (2012)
This study is aimed at discovering the portrayal of the voice of the people in the news photographs of The Jakarta Globe online newspaper. The data consist of 15 news photographs taken from The Jakarta Globe online newspaper published in January - October 2011. The study employs qualitative method framed with semiotic analysis using Roland Barthes' theory of orders of signification and photographic message (Barthes, 1977). The results of the study show that The Jakarta Globe visually constructs this event (demonstration) for the readers by focusing on the human action (the protesters). Therefore, the people's voices in the 15 photographs are represented in the form of actions performed by the people who are against Mubarak's government. Technically, the people's voices are also reflected in the photo subjects (the protesters) and the objects symbolism of the photo. Meanwhile, the technical aspects of the photo play a meaningful role in emerging the portrayal of the people's voice. There are 4 (four) voices revealed by the people in the 15 photographs, namely the voice of freedom in photo 1, 2, 3, and 4 (e.g. reflected in anger, the burning tire); the voice of peace in photo 6, 7, 8, and 10 (reflected in calmness, the flowers, the candle); the voice of justice in photo 5, 9, 13, 14, and 15 (reflected in the noose and the scale); and the voice of human rights in photo 12, 13, 14, and 15 (reflected in mourning, the coffin, and the blooded cloth). The photo text, including headlines and captions also interact with photographs to produce meaning in supporting the people's voices. The headlines tend to explain the people's voices implicitly, while the captions explicitly explain the people's voices. The results provided in this study should be considered as a starting point for discussion and not as a conclusive interpretation since there is no one a correct answer when interpreting an image. Thus, next researcher may combine qualitative method with quantitative method to get an objective result.